2020
DOI: 10.1101/2020.09.09.290361
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nanoparticle-mediated microRNA-145 Delivery for Vascular Smooth Muscle Cell Phenotype Modulation and Atherosclerosis Treatment

Abstract: Vascular smooth muscle cells (VSMCs) change from contractile to the synthetic phenotype during atherogenesis and 30-70% of cells that make up plaques have been elucidated to be of VSMC origin. MicroRNA-145 (miR-145) is responsible for regulating VSMC phenotypic switching, and low miR-145 levels in circulation have been linked with atherosclerosis. Hence, we developed nanoparticles for targeted delivery of miR-145 by synthesizing micelles co-assembled with miR-145 and the CCR2-binding peptides for plaque target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Cholesterol loading in mVSMC downregulates miR-143/145, resulting in the loss of the contractile phenotype, and miR-143/145 mimics protects against this loss 19 ; 3) Consistent with this, miR-143/145 expression is downregulated in aortic VSMCs in hypercholesterolemic apoE-/-mice 41,20 ; and, in epithelial and endothelial cells cholesterol loading attenuates TGFβ signaling 17,42 . The following series of experiments were performed, then, to test the model that cholesterol-loading reduces TGFβ signaling, which in turn decreases miR143/145 expression, resulting in the diminution of the contractile phenotype of hVSMCs.…”
Section: Tgfβ Signaling Is Downregulated In Cholesterol-loaded Hvsmcsmentioning
confidence: 79%
See 2 more Smart Citations
“…Cholesterol loading in mVSMC downregulates miR-143/145, resulting in the loss of the contractile phenotype, and miR-143/145 mimics protects against this loss 19 ; 3) Consistent with this, miR-143/145 expression is downregulated in aortic VSMCs in hypercholesterolemic apoE-/-mice 41,20 ; and, in epithelial and endothelial cells cholesterol loading attenuates TGFβ signaling 17,42 . The following series of experiments were performed, then, to test the model that cholesterol-loading reduces TGFβ signaling, which in turn decreases miR143/145 expression, resulting in the diminution of the contractile phenotype of hVSMCs.…”
Section: Tgfβ Signaling Is Downregulated In Cholesterol-loaded Hvsmcsmentioning
confidence: 79%
“…Notably, treatment with miR145 micelles rescued contractile marker expression to baseline levels. In the mouse study, treatment with miR145 micelles increased mVSMC contractile marker expression, collagen content and reduced necrotic core in both early atherosclerosis progression and in well-established disease 41 . One caveat is that the micelles target CCR2, which, in addition to macrophage-like mVSMCs, would also be expected to result in uptake by monocytes and macrophages.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Previous studies have reported that miRNA145 plays an important role in VSMCs lesions and phenotypic switching 70,71 .Moreover,it is believed that miRNA145 has become an effective way to treat cardiovascular diseases by regulating phenotypic switching.As early as 2009, a study published in nature showed that miRNA145 was a key factor regulating phenotype switching of VSMCs, which has high preventive and therapeutic value for acute myocardial infarction and hypertension 72 . In 2017, peiqiong zhou et al believed that miRNA145 could effectively regulate VSMCs phenotypic switching, and vascular stents containing miRNA145 could be used to prevent vascular tissue regeneration 73 .In2019,research suggested that miRNA-145 can regulate VSMCs in the normal contractile phenotype, and inhibit the excessive proliferation and intimal hyperplasia to cope wih the restenosis in small-diameter vascular regeneration 74 .In 2021, Deborah D Chin et al found that miR145 could rescue atherosclerotic protective systolic markers such as myocardium, α-SMA and calcitonin that synthesized in vitro, exerting its role in regulating phenotype transition and thus inhibiting the occurrence of atherosclerosis 75 . The most significantly altered pathway in VSMCs-specific NRF2 knockout mice is the MYOCD, which represents the phenotypic switching, so it is not difficult to guess the intermediate role played by miRNA145.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we developed PAMs using the CKDSPKSSKSIRFIPVST (CKD) peptide as our targeting moiety for the first time, which was previously reported to accumulate in the cortical collecting duct (CCD) of the kidneys, a region of therapeutic relevance as cyst formation is most prevalent in the CCD in ADPKD [ 20 ]. We encapsulated rapamycin, everolimus, or RapaLink-1, which is rapamycin chemically linked with MLN0128 [ 21 ] that can simultaneously bind to and inhibit both the FKBP12 region (via rapamycin) and the TOR kinase inhibitor (TORki)-binding region (via MLN0128) of mTORC1 [ 22 ]. We characterized the nanoparticle-drug formulations and evaluated their ability to inhibit cell proliferation in vitro in human CCD cells compared to free drug.…”
Section: Introductionmentioning
confidence: 99%